2017
DOI: 10.1002/adom.201600884
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Surface Plasmon Polariton Modes to Complementary THz Metasurfaces Tuned by Inter Meta‐Atom Distance

Abstract: The authors study the interaction of complementary terahertz (THz) split ring resonators with THz surface plasmon polaritons (SPPs) as a function of the meta-atom distance. The THz transmission properties of 15 samples for which the array dimensions are varied keeping the resonator shape constant are investigated. The linewidth of the inductive-capacitive (LC-)resonance is decreasing with increasing meta-atom distance, up to the frequency matching with the first SPP-mode. The SPP-mode couples to the narrow LC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 81 publications
1
38
0
Order By: Relevance
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclotron like polariton disappears for large detunings (spectra offset by 1.7% for clarity, dashed lines are a guide to the eye). Asterisks indicate plasmonic resonances arising from the periodicity of the SRR array [19]. For the large resonator structures lies also the broad l 2 inside the spectral range of the experiment.…”
mentioning
confidence: 99%
“…For example, this increases the resonance Q-factors of a simple split ring wire resonator supporting an inductive-capacitive (LC) mode and a quadrupole mode. Lattice mode coupling is very versatile and has been demonstrated on different types of metamaterial [35][36][37][38][39]41,42] and plasmonic resonances [16][17][18]34,43,[60][61][62][63][64][65][66][67][68][69][70][71][72]. This review highlights the SLR coupling to LC, dipole and hybridized modes of metamaterial resonators.…”
Section: High-q Resonancesmentioning
confidence: 99%
“…SLRs could be used to couple with the eigen or coupled resonances of metamaterial structures to show very interesting effects. These effects include extraordinary transmission, reduction of radiative losses for high quality (Q) factor resonances, electromagnetically induced transparency and strong coupling physics between SLRs and metamaterial resonances [35][36][37][38][39][40][41][42][43]. For a long time, the terahertz region of electromagnetic spectrum was being referred to as technological gap between the infrared and microwave frequencies, which required more efficient and compact terahertz devices, sources and detectors [44].…”
Section: Introductionmentioning
confidence: 99%